MYB oncoproteins: emerging players and potential therapeutic targets in human cancer - Cicirò, Ylenia; Sala, Arturo (Oncogenesis (New York, NY), 2021)
MYB transcription factors are highly conserved from plants to vertebrates, indicating that their functions embrace fundamental mechanisms in the biology of cells and organisms. In humans, the MYB gene family is composed of three members: MYB , MYBL1 and MYBL2 , encoding the transcription factors MYB, MYBL1, and MYBL2 (also known as c-MYB, A-MYB, and B-MYB), respectively. A truncated version of MYB, the prototype member of the MYB family, was originally identified as the product of the retroviral oncogene v-myb , which causes leukaemia in birds. This led to the hypothesis that aberrant activation of vertebrate MYB could also cause cancer. Despite more than three decades have elapsed since the isolation of v-myb, only recently investigators were able to detect MYB genes rearrangements and mutations, smoking gun evidence of the involvement of MYB family members in human cancer. In this review, we will highlight studies linking the activity of MYB family members to human malignancies and experimental therapeutic interventions tailored for MYB -expressing cancers.